Alignment of Training Curriculum and Surgical Practice: Implications for Competency, Manpower, and Practice Modeling - Sømme, S.; Bronsert, M.; Kempe, A.; Morrato, E. H.; Ziegler, M. (European Journal of Pediatric Surgery, 2012)
Objective The attractiveness of pediatric surgery (PS) as a specialty includes its primary role in the care of multisystemic disease. We were interested in identifying changes in operative case quality and quantity when comparing PS residents to PS practitioners.Methods The 2006 Accreditation Council for Graduate Medical Education PS resident current procedural terminology (CPT) code database (26,077 resident cases) was merged with the 2006 Kids' Inpatient Database of International Classification of Diseases (ICD)-9 procedure codes (230,504 practitioner cases) and categorized by case type and volumes according to a resident CPT reference file. Cases were categorized into 84 procedure types. A recent estimate of 691 practicing pediatric surgeons was used as denominator to calculate case volume per surgeon. Our analysis focused on the PS index cases and we compared PS residents to subspecialty board certified general pediatric surgeons in practice. We excluded cases that may be performed by general surgeons without PS training.Results Our data indicate that, on average, 501 cases are performed annually by each PS resident. We identified significant differences in case volume per surgeon between training and practice for most PS index cases.Conclusions The PS index case quantity declined significantly from training to practice. If a volume to outcome relationship applies to these complex and infrequent PS cases, then to sustain and improve clinical quality post-training will require a new paradigm of continued learning. Additionally, a relook at the optimal manpower and more focused regionalization is warranted.
Keywords: pediatric surgery training; surgical volume; competency